Synthesis and device properties of carbazole/benzimidazole-based host materials. Issue 37 (13th September 2017) - Hu, Mingming; Song, Wenxuan; Huang, Jinhai; Xia, Zhenyuan; Su, Jianhua
Graphical abstract: Highlights: Carbazole/benzimidazole derivatives were synthesized and characterized. The derivatives were found to be potential red host materials for PhOLEDs. The two novel host materials exhibited high thermal stabilities about 450 °C. Both of them revealed balanced charge transport. Abstract: We report two bipolar host materials bearing hole-transport benzofurocarbazole/indenocarbazole cores and an electron-transport benzimidazole moiety for red phosphorescence organic light emitting devices (PhOLEDs). The two novel host materials exhibited excellent physical properties with high thermal stabilities, appropriate HOMO-LUMO energy levels and balanced charge transport. Both of them were applied to fabricate red PhOLEDs as promising host materials, and 7, 7-dimethyl-5-(4′-(1-phenyl-1 H -benzo[ d ]imidazol-2-yl)-[1, 1′-biphenyl]-4-yl)-5, 7-dihydroindeno[2, 1- b ]carbazole (ICBI ) based device demonstrated outstanding electroluminescence performance with the maximum current efficiency, power efficiency and external quantum efficiency of 33.0 cd/A, 13.9 lm/W and 18.9%, respectively.